2018
DOI: 10.1158/2326-6066.cir-18-0065
|View full text |Cite
|
Sign up to set email alerts
|

CD30-Redirected Chimeric Antigen Receptor T Cells Target CD30+ and CD30− Embryonal Carcinoma via Antigen-Dependent and Fas/FasL Interactions

Abstract: Tumor antigen heterogeneity limits success of chimeric antigen receptor (CAR) T-cell therapies. Embryonal carcinomas (EC) and mixed testicular germ cell tumors (TGCT) containing EC, which are the most aggressive TGCT subtypes, are useful for dissecting this issue as ECs express the CD30 antigen but also contain CD30 cells. We found that CD30-redirected CAR T cells (CD30.CAR T cells) exhibit antitumor activity against the human EC cell lines Tera-1, Tera-2, and NCCIT and putative EC stem cells identified by Hoe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 50 publications
1
49
0
Order By: Relevance
“…More recently, FasL on CAR T cells has been shown to induce embryonal carcinoma death independent of target antigen expression, especially after Fas was ectopically expressed in the tumor. 31 We found that another death-inducing ligand, Figure 3. Sensitizing RT Transcriptionally Primes Pancreatic Cancer Cells for TRAIL-Induced Death (A) RNA expression levels of signaling molecules known to mediate various TRAIL responses, including survival and migration, tumor-supportive inflammation, necroptosis, apoptosis, and death receptor endocytosis, were quantified by RNA-seq before and after RT exposure to Capan2 pancreatic cancer cells in three biologic replicates.…”
Section: Discussionmentioning
confidence: 89%
“…More recently, FasL on CAR T cells has been shown to induce embryonal carcinoma death independent of target antigen expression, especially after Fas was ectopically expressed in the tumor. 31 We found that another death-inducing ligand, Figure 3. Sensitizing RT Transcriptionally Primes Pancreatic Cancer Cells for TRAIL-Induced Death (A) RNA expression levels of signaling molecules known to mediate various TRAIL responses, including survival and migration, tumor-supportive inflammation, necroptosis, apoptosis, and death receptor endocytosis, were quantified by RNA-seq before and after RT exposure to Capan2 pancreatic cancer cells in three biologic replicates.…”
Section: Discussionmentioning
confidence: 89%
“…To detect the side population (SP) cells, Hoechst 33342 samples were excited using a 355 nm UV laser on a LSRII/Fortessa flow cytometer (BD Biosciences; refs. 21,22).…”
Section: Side Population Staining By Hoechst Dyementioning
confidence: 99%
“…Further investigation of CDK4/6 inhibition for the treatment of teratoma is required based on the preliminary results indicating the safety and potential clinical benefit [ 115 ]. Similarly, immune checkpoint inhibitors in MOGCTs need to be unraveled [ 115 , 116 ].…”
Section: Management Of Malignant Ovarian Germ Cell Tumors (Mogcts)mentioning
confidence: 99%